Exogenous acetic acid pre-treatment increases drought tolerance of two Indonesian foxtail millet (Setaria italica) accessions - Choirotin Nisa; Nurul Jadid (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nisa C, Jadid N. 2021. Exogenous acetic acid pre-treatment increases drought tolerance of two Indonesian foxtail millet (Setaria italica) accessions. Biodiversitas 22: 2117-2124. Drought is one of the external factors that affect the productivity of food crops. Some biotechnological approaches had been developed to increase plant resistance to drought stress. Moreover, an adjustment in plant cultivation system is also reported as alternative way to enhance plant resistance to water deficit conditions, especially during their initial vegetative phase. This study aimed to determine the effect of exogenous acetic acid pre-treatment on some Indonesian foxtail millet (Setaria italica) accessions under drought stress conditions. Two different foxtail millet accessions were used in this study: Gambir Manis and Polman Kuning. Morphological and physiological parameters were observed during this study, including plant height, number of leaves, root length, relative water content, total chlorophyll and carotenoid content, and panicle weight. Our results showed that all foxtail millet accessions survived drought stress condition after being pre-treated with exogenous acetic acid. Yet, some morphological parameters were significantly affected. Meanwhile, physiological parameters were not significantly affected. Overall, our data suggest that exogenous acetic acid pre-treatment could enhance drought avoidance in S. italica accessions. This might be due to acetic acid-induced jasmonic acid modulation and secondary metabolites production in S. italica during water deficit exposure.